Academic Senate Minutes 2008-10-16 - Academic Senate:::::::::
Chair report. Approval of Agenda. Associated Students report. Approval of minutes postponed. Vice President of Administration and Finance report. Ad-Hoc Diversity Committee report. Statewide Senators report. CFA Chapter President report. WASC Discussion of Coalescing Planning Processes.